Analysis Of Capital Expenditure Recording In Asset Management At The Department Of Education And Culture City Of Parepare - Nadilla Mursalim; Adhy Wijaya (Journal AK-99, 2023)
Problems that arise in realizing quality local government financial reports are asset management problems. The phenomenon of the audit results of the Supreme Audit Agency (BPK) on local government financial reports that give the predicate of fair, unreasonable or disclaimer of opinion, is more often caused by asset management problems. In certain cases, there are regions that experience a decrease in opinion from Unqualified (WTP) to Unqualified (WDP), or do not provide an opinion (disclaimer) due to their inability to realize good governance of local government assets. Based on this phenomenon, the objectives to be achieved from this research include: To find out the form of accounting records and asset management systems used for capital expenditures at the Department of Education and Culture of Parepare City. The approach to the method used in this study is the Qualitative Method, while the results of the analysis obtained include: Management of Regional Assets or Property carried out by the Education and Culture Office of the City of Parepare in general using the Accrual Basis method, the recording mechanism carried out by the Property Manager on The Office of Education and Culture of Parepare City, in general, can be said to have not run optimally, because it has not fully understood the rules for recognizing capital expenditures in laws and regulations and the administrative mechanism carried out by the Office of Education and Culture of Parepare City, it is necessary to pay attention to the management structure. goods at the OPD level, where the Auxiliary Goods Manager has not yet been determined, both at the OPD and UPTD levels